Proteomic Studies on the Mechanism of Myostatin Regulating Cattle Skeletal Muscle Development - Sheng, Hui; Guo, Yiwen; Zhang, Linlin; Zhang, Junxing; Miao, Manning; Tan, Haoyun; Hu, Debao; Li, Xin; Ding, Xiangbin; Li, Guangpeng; Guo, Hong (Frontiers in Genetics, 2021)
Myostatin (MSTN) is an important negative regulator of muscle growth and development. In this study, we performed comparatively the proteomics and phosphorylated proteomics analyses of gluteus tissues from MSTN+/- Mongolian cattle (MG.MSTN+/-), wild type Mongolian cattle (MG.WT) and Belgian Blue cattle (BBC) using a shotgun-based tandem mass tag (TMT) 10-plex labeling method to investigate the regulation mechanism of MSTN on the growth and development of bovine skeletal muscle. A total of 1950 proteins and 713 phosphorylated peptides corresponding to 268 phosphorylated proteins were identified in MG.MSTN+/-, MG.WT and BBC. Among them, 320 differentially expressed proteins and 54 differentially altered phosphorylated peptides corresponding to 37 phosphorylated proteins were identified in MG.MSTN+/- compared with MG.WT; and 376 differentially expressed proteins and 87 differentially altered phosphorylated peptides corresponding to 46 phosphorylated proteins were identified in BBC compared with MG.WT; compared with MG.MSTN+/-, 350 differentially expressed proteins, and 6 differentially altered phosphorylated peptides corresponding to 6 phosphorylated proteins were identified in BBC. Bioinformatics analysis showed that knockdown of MSTN gene increased the expression of extracellular matrix and ribosome-related proteins, induced activation of focal adhesion, PI3K-AKT, and Ribosomal pathways. The results of proteomic analysis were verified by muscle tissue Westernblot test and in vitro MSTN gene knockdown test, and it was found that knockdown MSTN gene expression could promote the proliferation and myogenic differentiation of bovine skeletal muscle satellite cells (BSMSCs). At the same time, Co-Immunoprecipitation (CO-IP) assay showed that MSTN gene interacted with extracellular matrix related protein type I collagen α 1 (COL1A1), and knocking down the expression of COL1A1 could inhibit the activity of adhesion, PI3K-AKT and ribosome pathway, thus inhibit BSMSCs proliferation. These results suggest that the MSTN gene regulates focal adhesion, PI3K-AKT, and Ribosomal pathway through the COL1A1 gene. In general, this study provides new insights into the regulatory mechanism of MSTN involved in muscle growth and development.